Engineered drug delivery devices to address Global Health challenges - Sadeghi, Ilin; Byrne, James; Shakur, Rameen; Langer, Robert (Journal of controlled release, 2021)
There is a dire need for innovative solutions to address global health needs. Polymeric systems have been shown to provide substantial benefit to all sectors of healthcare, especially for their ability to extend and control drug delivery. Herein, we review polymeric drug delivery devices for vaccines, tuberculosis, and contraception. [Display omitted]